Model kurikulum sui generis pesantren dalam merespon tantangan pendidikan Islam kontemporer - Khanifah, Khanifah; Anggraini, Nurhaliza; Syam, Robingun Suyud El (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This article examines the sui generis model of pesantren curriculum in responding to the challenges of contemporary Islamic education, particularly in relation to state policy and institutional legitimacy. This qualitative field-based study was conducted at Pondok Pesantren Al-Asy‘ariyyah Kalibeber, Wonosobo, Central Java, using a reflective-institutional approach. Data were collected through in depth interviews, classroom observations, and institutional document analysis, and analyzed thematically. The findings reveal that the pesantren curriculum demonstrates a strong sui generis character manifested in curricular autonomy, flexible learning structures, and selective adaptation to formal educational regulations. Rather than passively accommodating modernity, the pesantren actively negotiates its position with the state while maintaining its traditional epistemological foundations. This study contributes to the discourse on pesantren state relations by highlighting the curriculum as a strategic space for institutional negotiation within contemporary Islamic education in Indonesia.